In situ polymerization of poly aniline—SPEEK-PMA-based proton exchange membrane for DMFC application. (February 2021) - Arul Joseph Helen Therese, JB; Selvakumar, K; Gayathri, R; Ramesh Prabhu, M; Sivakumar, P
Composite membranes based on sulfonated poly (ether ether ketone) (SPEEK)/phosphomolybdic acid (PMA) have been prepared by solution casting technique. SPEEK/PMA membrane surfaces are modified with polyaniline (PANI) by in situ polymerization. The structural and electrochemical properties of the surface modified membranes are studied by atomic force microscopy (AFM), Fourier transform infrared, nuclear magnetic resonance, water uptake, ion-exchange capacity, proton conductivity, methanol permeability, and tensile strength. The AFM image shows that the hetero polyacids are better compatible with SPEEK matrix. The SPEEKs/PMAs membranes achieved acceptable proton conductivity with increasing in weight ratios of PMAs and reached highest proton conductivity of 5.5 × 10 −3 S cm −1 at room temperature. With Lower swelling ratio, high thermal stability, proton conductivity, and relative selectivity, SPEEKs/PMAs-PANI membranes can be a promising material as Proton Exchange Membrane (PEM) for Direct Methanol Fuel Cell (DMFC) applications.